Loss of Grhl3 is correlated with altered cellular protrusions in the non‐neural ectoderm during neural tube closure. Issue 5 (9th January 2021) - Jaffe, Eric; Niswander, Lee
Abstract: Background: The transcription factor Grainyhead‐like 3 (GRHL3) has multiple roles in a variety of tissues during development including epithelial patterning and actin cytoskeletal regulation. During neural tube closure (NTC) in the mouse embryo, GRHL3 is expressed and functions in the non‐neural ectoderm (NNE). Two important functions of GRHL3 are regulating the actin cytoskeleton during NTC and regulating the boundary between the NNE and neural ectoderm. However, an open question that remains is whether these functions explain the caudally restricted neural tube defect (NTD) of spina bifida observed in Grhl3 mutants. Results: Using scanning electron microscopy and immunofluorescence based imaging on Grhl3 mutants and wildtype controls, we show that GRHL3 is dispensable for NNE identity or epithelial maintenance in the caudal NNE but is needed for regulation of cellular protrusions during NTC. Grhl3 mutants have decreased lamellipodia relative to wildtype embryos during caudal NTC, first observed at the onset of delays when lamellipodia become prominent in wildtype embryos. At the axial level of NTD, half of the mutants show increased and disorganized filopodia and half lack cellular protrusions. Conclusion: These data suggest that altered cellular protrusions during NTC contribute to the etiology of NTD in Grhl3 mutants. Key Findings: Loss of Grhl3 leads to altered cellular protrusions in the non‐neural ectoderm during neural tube closure Loss of Grhl3 does not cause loss of epithelial state in the non‐neural ectoderm during neural tube closure Loss of Grhl3 does not result in altered NNE identity or morphology during neural tube closure